Computer Technology and Students’ Social Cultural Values in Selected Secondary Schools in Kabale District. - Ninsiima, Comfort (Kabale University, 2024)
This study utilizes a descriptive research design that integrates quantitative and qualitative methodologies to investigate how technology affects cultural beliefs and social behaviors among secondary students in selected schools within the Kabale District. The research encompasses 20 students, 5 administrators, and 5 IT teachers, ensuring representation across key stakeholders in the educational setting. Structured surveys are employed to collect quantitative data, focusing on the frequency of technology usage, perceived positive and negative impacts, and home access to technology. Additionally, in-depth interviews are conducted with administrators and IT teachers to gather qualitative insights into the integration of technology and its influence on students' socio-cultural values. The main objectives of the study are to examine the dual impact of technology on students' socio-cultural values and to propose strategies for balanced technology integration that respects cultural heritage and ethical principles. Through a combined approach of surveys and interviews, the research aims to explore the complex relationship between technology use and cultural beliefs, illuminating how digital tools shape social behaviors and cultural identity among secondary students. By employing a mixed-methods approach, this study aims to offer a comprehensive understanding of the diverse impacts of technology on socio-cultural values in secondary education. The findings from this research endeavor have the potential to inform educational policies, guide curriculum development, and influence teaching practices, with the overarching aim of promoting a harmonious integration of technology that upholds cultural diversity and ethical considerations.